Circulating microRNA‐22 correlates with microRNA‐122 and represents viral replication and liver injury in patients with chronic hepatitis B1. Issue 5 (18th March 2013) - Arataki, Keiko; Hayes, C. Nelson; Akamatsu, Sakura; Akiyama, Rie; Abe, Hiromi; Tsuge, Masataka; Miki, Daiki; Ochi, Hidenori; Hiraga, Nobuhiko; Imamura, Michio; Takahashi, Shoichi; Aikata, Hiroshi; et al.
Abstract Hepatitis B virus (HBV) infection is associated with increased expression of microRNA‐122. Serum microRNA‐122 and microRNA‐22 levels were analyzed in 198 patients with chronic HBV who underwent liver biopsy and were compared with quantitative measurements of HBsAg, HBeAg, HBV DNA, and other clinical and histological findings. Levels of serum microRNA‐122 and microRNA‐22 were determined by reverse transcription‐TaqMan PCR. Serum levels of microRNA‐122 and microRNA‐22 were correlated (R2 = 0.576; P < 0.001), and both were elevated in chronic HBV patients. Significant linear correlations were found between microRNA‐122 or microRNA‐22 and HBsAg levels (R2 = 0.824, P < 0.001 and R2 = 0.394, P < 0.001, respectively) and ALT levels (R2 = 0.498, P < 0.001 and R2 = 0.528, P < 0.001, respectively). MicroRNA‐122 levels were also correlated with HBV DNA titers (R2 = 0.694, P < 0.001 and R2 = 0.421, P < 0.001). Levels of these microRNAs were significantly higher in HBeAg‐positive patients compared to HBeAg‐negative patients (P < 0.001 and P < 0.001). MicroRNA‐122 levels were also lower in patients with advanced liver fibrosis (P < 0.001) and lower inflammatory activity (P < 0.025). These results suggest that serum micro‐RNA levels are significantly associated with multiple aspects of HBV infection. The biological meaning of the correlation between microRNA‐122 and HBsAg and should be investigated further. J. Med. Virol. 85:789–798, 2013. © 2013 Wiley Periodicals, Inc.